Report on the Observance of Standards and Codes, Accounting and Auditing : Module A - Accounting and Auditing Standards, A.1 Financial Reporting Standards Analysis - World Bank (World Bank, Washington, DC, 2017)
The quality of financial reporting depends to a great extent on the quality of the Accounting and Auditing (A&A) standards on which the reporting is based. Accounting standards are seen as a critical language of business. In countries seeking to improve their business environment to attract foreign direct investment and mobilize savings and finance to support productive and job-creating activities, if national accounting standards differ significantly from the increasingly universal international benchmark, International Financial Reporting Standards (IFRS), it becomes difficult for foreign investors to understand the financial reports of domestic companies, thus potentially hampering investment and growth. The objective of the financial reporting standards analysis is to compare national financial reporting standards (or generally accepted accounting principles - national (GAAP) with IFRS with a view to capturing significant differences (where applicable) in order to provide: (a) readers with a clear sense of where key areas of divergence lie, and (b) country counterparts with concrete suggestions for improving national GAAP and aligning them to the extent possible with IFRS.